In vitro and in vivo quality of leukoreduced apheresis platelets stored in a new platelet additive solution. Issue 5 (6th August 2012) - Dumont, Larry J.; Cancelas, Jose A.; Graminske, Sharon; Friedman, Kenneth D.; Vassallo, Ralph R.; Whitley, Pamela H.; Rugg, Neeta; Dumont, Deborah F.; Herschel, Louise; Siegal, Alan H.; Szczepiorkowski, Zbigniew M.; Fender, Logan; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND: Platelets (PLTs) stored in additive solutions (PASs) may reduce the risk of several plasma‐associated adverse transfusion reactions such as allergic reactions and potentially transfusion‐associated lung injury. The objective of this study was to determine the in vitro characteristics and the in vivo radiolabeled recovery and survival of apheresis PLTs (APs) stored in a new PAS and compare the latter to Food and Drug Administration (FDA) criteria. STUDY DESIGN AND METHODS: Hyperconcentrated APs were collected from healthy subjects in a paired crossover study comparing PAS (35% plasma) and 100% plasma‐stored APs (Part 1) up to 7 days and, in Part 2, to determine the in vivo recovery and survival of PAS stored AP at 5 days compared to fresh PLT controls. In vitro and in vivo assays were performed following standard methods. RESULTS: Sixty‐six and 25 evaluable subjects successfully completed Parts 1 and 2, respectively. pH for PAS AP was maintained above 6.6 for 5 days of storage. P‐selectin values were consistent with published values for commonly transfused PLT products. The PAS in vivo PLT recovery (54.3 ± 8.1%) was 86.7% of the fresh control, and survival (6.4 ± 1.3 days) was 78.0% of the fresh control, both meeting the FDA performance criteria. CONCLUSION: APs stored in PAS with 35% plasma carryover maintained pH over 5 days of storage and met current FDA criteria for radiolabeled recovery and survival. The use of PAS for storage of single‐donor PLTs in clinical practice represents an acceptable transfusion product that reduces the volume of plasma associated with PLT transfusion.